Light-induced modulation of the mitochondrial respiratory chain activity: possibilities and limitations - Lunova, Mariia; Smolková, Barbora; Uzhytchak, Mariia; Janoušková, Klára Žofie; Jirsa, Milan; Egorova, Daria; Kulikov, Andrei; Kubinová, Šárka; Dejneka, Alexandr; Lunov, Oleg (Cellular and molecular life sciences, 2020)
Biological effects of high fluence low-power (HFLP) lasers have been reported for some time, yet the molecular mechanisms procuring cellular responses remain obscure. A better understanding of the effects of HFLP lasers on living cells will be instrumental for the development of new experimental and therapeutic strategies. Therefore, we investigated sub-cellular mechanisms involved in the laser interaction with human hepatic cell lines. We show that mitochondria serve as sub-cellular "sensor" and "effector" of laser light non-specific interactions with cells. We demonstrated that despite blue and red laser irradiation results in similar apoptotic death, cellular signaling and kinetic of biochemical responses are distinct. Based on our data, we concluded that blue laser irradiation inhibited cytochrome c oxidase activity in electron transport chain of mitochondria. Contrary, red laser triggered cytochrome c oxidase excessive activation. Moreover, we showed that Bcl-2 protein inhibited laser-induced toxicity by stabilizing mitochondria membrane potential. Thus, cells that either overexpress or have elevated levels of Bcl-2 are protected from laser-induced cytotoxicity. Our findings reveal the mechanism how HFLP laser irradiation interfere with cell homeostasis and underscore that such laser irradiation permits remote control of mitochondrial function in the absence of chemical or biological agents.
Keywords: Gene Expression Regulation; Reactive oxygen species (ROS); Mitochondrial membrane potential (ΔmΦ); Photobiomodulation; Mitochondria; viabilita buněk; laserová terapie s nízkou intenzitou světla; reaktivní formy kyslíku; buňky Hep G2; Phototoxicity; mitochondriální membrány; Cell Survival; transport elektronů; respirační komplex IV; High fluence low-power laser irradiation; Electron Transport Complex IV; oxidace-redukce; Reactive Oxygen Species; Electron Transport; lidé; Humans; Phototherapy; regulace genové exprese; Hep G2 Cells; apoptóza; Low-Level Light Therapy; membránový potenciál mitochondrií; Oxidation-Reduction; Mitochondrial Membranes; fototerapie; Membrane Potential, Mitochondrial; mitochondrie; Apoptosis